"So she might know her beauty": Creating safe spaces for Black girls in the middle grades. Issue 4 (8th August 2021) - Dolet, Tia C.; Salas, Spencer
Abstract: Leveraging the momentum of the #MeToo and #BlackLivesMatter movements as a call for change, this piece focuses on how middle grades communities can better support and protect their Black female students. Coming together as middle grades teacher leaders, we took up The Bluest Eye as the starting point for a discussion of these issues. Grounded in interdisciplinary scholarship and practice, this piece shares anecdotes from our staff book club session to create a working outline for how middle grades might begin to build safer environments for the Black girls in our classrooms and communities.